PERAN SUPERVISI KOLABORATIF UNTUK MENINGKATKAN PROFESIONALIME GURU DALAM PENERAPAN KURIKULUM BERBASIS CINTA DI MADRASAH - Alfisyah (AT-TAKLIM: Jurnal Pendidikan Multidisiplin, 2026)
With the Love-Based Curriculum already implemented at MAN Kota Banjarbaru, this research intends to examine how collaborative academic supervision could improve teachers' professionalism. A case study design was used in the research, which was qualitative in nature. Teachers, the administrator, and the VP of curriculum affairs participated in in-depth interviews and document analyses to compile the data. Triangulation of sources and techniques guaranteed data validity as we thematically analyzed the data utilizing an interactive analysis model that included data reduction, data presentation, and conclusion drafting. Together, supervisors and instructors engaged in collaborative academic supervision, according to the results. This included open classroom observations, reflective conversations, and cooperative planning. These supervisory practices were associated with the strengthening of teacher professionalism, particularly in pedagogical competence, professional competence, and reflective teaching attitudes. Furthermore, collaborative supervision supported the implementation of the Love-Based Curriculum by guiding teachers to integrate values of empathy, humanism, and character education into classroom practices. This study concludes that collaborative supervision plays a strategic role as a professional development approach for teachers and as a key mechanism in supporting the implementation of value-based curricula in madrasahs.